2017
DOI: 10.3390/en10122006
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of a Desiccant Dehumidifier with a Heat Recovery Unit

Abstract: Abstract:In order to effectively increase the drying rate and reduce the energy consumption, a dryer which reduces the air humidity at the dryer inlet using desiccant and regenerates the desiccant by recovering waste heat using a heat pipe heat exchanger was developed in this study. Both the adsorption rate and desorption rate of the dryer were measured at several ambient temperatures ranging from 15 • C to 35 • C, relative humidity levels of air ranging from 20% to 85%, and airflow rates ranging from 30 m 3 /… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Internal heat recovery increases the dehumidifier performance. 101,102 Wang et al reached an SY water of 0.84 L kW −1 h −1 by using LiCl enclosed in an active carbon felt matrix as adsorbent and an electric heater for the discontinuous desorption stage. 95 The high efficiency can be explained by the humid conditions under which this excellent performance was achieved in combination with an efficient heater.…”
Section: Environmental Science: Water Research and Technology Critical mentioning
confidence: 99%
“…Internal heat recovery increases the dehumidifier performance. 101,102 Wang et al reached an SY water of 0.84 L kW −1 h −1 by using LiCl enclosed in an active carbon felt matrix as adsorbent and an electric heater for the discontinuous desorption stage. 95 The high efficiency can be explained by the humid conditions under which this excellent performance was achieved in combination with an efficient heater.…”
Section: Environmental Science: Water Research and Technology Critical mentioning
confidence: 99%
“…In these studies, the exhaust temperature of the gases is generally over 90 • C [3]. Yang et al proposed a novel heat pipe-based desiccant device [4]. Galindo et al analyzed some models based on an experimental Organic Rankine Cycle (ORC) in a turbocharged 2.0 L gasoline engine, using the waste heat recovery, and they found that the effect was good [5].…”
Section: Introductionmentioning
confidence: 99%
“…The quality of energy supplied to the adsorption system is critical as it is dictated by the unique interaction of the adsorbent-adsorbate pair and the adsorption energy sites that are available to the adsorbate molecules. In adsorption dehumidification, the quality and amount of energy required for regeneration depends upon adsorption energy sites that capture adsorbate molecules from the mainstream (Yang K. S. et al, 2017 ; Yang W. et al, 2017 ; Burhan et al, 2018b ).…”
Section: Introductionmentioning
confidence: 99%